2018
DOI: 10.2495/hpsm180141
|View full text |Cite
|
Sign up to set email alerts
|

Towards Optimum Design for Crack Width Limit States: The Need for Further Developments

Abstract: Serviceability limit states including cracking are of increasing importance and often dominate the design of reinforced concrete structures. Furthermore, actual crack widths and their shape play an important role in the assessment of service life of existing reinforced concrete structures. Crack width is inherently a random variable of considerable scatter due to randomness of material properties, geometry of the structure, loading and model uncertainty in crack width estimates. The state-of-the-art concepts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Most research into reliability in WRS and crack widths in general consider a limit state of the difference between a deterministic target crack width and the crack width achieved using a code crack prediction model. A number of previous research projects employed this approach 4,8,23–25 and reported the reliability that each respective design code crack prediction model achieved for deterministic target crack widths ranging from 0.1 to 0.4 mm. All the investigated crack prediction models were reported to have adequate levels of SLS reliability; 0β and 1.5β for reversible and irreversible concrete cracking, respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Most research into reliability in WRS and crack widths in general consider a limit state of the difference between a deterministic target crack width and the crack width achieved using a code crack prediction model. A number of previous research projects employed this approach 4,8,23–25 and reported the reliability that each respective design code crack prediction model achieved for deterministic target crack widths ranging from 0.1 to 0.4 mm. All the investigated crack prediction models were reported to have adequate levels of SLS reliability; 0β and 1.5β for reversible and irreversible concrete cracking, respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Most often, these target crack widths are empirical, stemming from qualitative satisfactory performance over the years, rather than a target reliability. 4 As such, reliabilities achieved by using these target crack widths have not been quantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation